Lexical Richness in Scientific Journal Articles: A Comparison between ESL and EFL Writers - Sumit Choemue; Barli Bram (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
This study investigated lexical richness in research articles published by writers of ESL and EFL in the ASEAN countries. The question was whether there were any significant similarities and differences in terms of lexical richness in research articles between these two groups. The researchers employed three different lexical measures to find out the answer: (a) lexical density (how many content words were used), (b) lexical diversity (how wide-ranging words were used), and (c) lexical sophistication (how many advanced and unusual words were used). The primary data consisted of 40 research articles published by two ESL countries, namely Malaysia and the Philippines, and the other two EFL countries: Indonesia and Thailand and were taken from the Directory of Open Access Journals (DOAJ) and Bielefeld Academic Search Engine (BASE). The researchers analyzed the data by utilizing three measurement tools namely CLAWS Tagger, Moving-Average-Type-Token-Ratio (MATTR), and VocabProfiler, and compared the results between ESL and EFL using the Mann-Whitney U test. Interestingly, despite different total tokens in several aspects, the data analysis results indicated no significant difference between ESL and EFL writers in terms of lexical richness and how they employed vocabulary in their research articles. This study further discussed factors influencing the use of vocabulary by two groups and concluded with limitations of the study and future research directions.